Penerapan Metode Tandur dan Melempar “Bola Salju” (T & BS) untuk Meningkatkan Hasil Belajar pada Siswa SDN 8 Jenggik - Suhaili Munahar (LP2M STIT Palapa Nusantara, 2016)
This study aims to improve student learning outcomes SDN 8 Jenggik through the application of methods of T & BS. Based on observations and interviews with teachers of grades there are some problems at the time of learning as the low student learning, lack of attention to students' learning process. To overcome the existing problems teachers should improve the system of learning one way to apply the method Tandur and throws a